Professional Identity in Narratives - Gabriela Chefneux (Acta Universitatis Sapientiae: Philologica)
The paper analyses six professional narratives in a workplace meeting. The first part presents the theoretical framework, namely definition, types of and approaches to identity and the main features of narratives, namely the structure, function, and narrator’s roles. The underlying assumption is that speakers display particular facets of their identity considering the environment and the type of interaction in which they are engaged and that narratives change depending on their purpose and context. The theoretical framework relies on Tajfel’s social constructionist approach to identity and on the Membership Categorization Analysis. The second part is the data analysis of the narratives presented by several employees of a multinational company during a phone conference meeting, with a focus on the professional identity in terms of narrative structure and values upheld by the narrators. The analysis presents the structure of the professional narratives, the values upheld, and the narrators’ roles and concludes with a possible professional master narrative.